2005
DOI: 10.3354/dao065181
|View full text |Cite
|
Sign up to set email alerts
|

Possible modes of dissemination of the amphibian chytrid Batrachochytrium dendrobatidis in the environment

Abstract: Amphibian chytridiomycosis caused by Batrachochytrium dendrobatidis has spread at an alarming rate over large distances throughout sensitive frog populations in eastern Australia, Central America and New Zealand. Infected amphibians and contaminated water are implicated in translocation, but other vectors are unknown. Through in vitro studies we show that potential means of translocation may be moist soil and bird feathers. B. dendrobatidis survived for up to 3 mo in sterile, moist river sand with no other nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
138
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 16 publications
2
138
1
3
Order By: Relevance
“…However, this seems unlikely. The effects of rates of physical contact between frogs on rates of transmission of B. dendrobatidis are not known, but frogs can also become infected by contact with water or substrates, both of which can harbour infectious B. dendrobatidis zoospores [48,49]. In addition, zoospores can be carried and released into the environment by non-amphibian hosts, including nematodes and crayfish [50,51], and non-amphibian reservoirs, including reptiles and waterfowl [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, this seems unlikely. The effects of rates of physical contact between frogs on rates of transmission of B. dendrobatidis are not known, but frogs can also become infected by contact with water or substrates, both of which can harbour infectious B. dendrobatidis zoospores [48,49]. In addition, zoospores can be carried and released into the environment by non-amphibian hosts, including nematodes and crayfish [50,51], and non-amphibian reservoirs, including reptiles and waterfowl [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…As prevalence increases within the amphibian community, diseased frogs shed zoospores into the environment or directly pass them to other amphibians by contact. In the laboratory, B. dendrobatidis zoospores remain viable for at least 3 mo in sterile sand or bird feathers (21), and infected frogs and salamanders can carry an infection 24-220 days before dying, with animals at cooler temperatures shedding zoospores over a longer period (refs. 22, 23, and V. Miera, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that B. dendrobatidis can be carried on algae (12), terrestrial reptiles (19), waterfowl (20), and nematodes (21), but there is currently no evidence that these carriers actually supported pathogen growth or transmission, which would be necessary to explain the long-term persistence of B. dendrobatidis in the absence of amphibians. Other studies have grown B. dendrobatidis on boiled snake skin (11,22), sterilized bird feathers (23), and toe scales from waterfowl (20), but none of these studies demonstrated B. dendrobatidis growth on live hosts with functioning immune systems. Consequently, we lack studies that demonstrate B. dendrobatidis growth on living, nonamphibian hosts, transmission of B. dendrobatidis from these hosts to amphibians, and links between nonamphibian hosts and B. dendrobatidis prevalence in the field.…”
mentioning
confidence: 99%